Implementasi Pendidikan Karakter Dalam Membentuk Kesantunan Berbahasa Di Lingkungan Sekolah Dasar - Rahmad, Ilmi Noor; Yudha, Chrisnaji Banindra; Canendia, Faradila; Rohmatin, Sayli Alvi; Pratiwi, Phia Loka; Alfian (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Character education important to develop elementary school students, in order to develop habits of thinking and behavior that help students face and overcome problems in their lives both in the school environment and society. STKIP Kusuma Negara Elementary School Teacher Education Study Program through the KKL Course held a webinar with the theme The Role of Teachers in Implementing Character Education in Elementary Schools. This webinar was held through the zoom meeting and was attended by 425 participants, consisting of elementary school teachers, education practitioners and students of STKIP Kusuma Negara and the general public. The purpose of this training to provide an understanding of the importance of character education for students at primary school age and provide strategies so that teachers can develop character education effectively. The webinar materials are Language Politeness in the Implementation of Character Education and Teachers in the Implementation of Character Education in Elementary Schools.